Augmenting effects of gestational arsenite exposure of C3H mice on the hepatic tumors of the F2 male offspring via the F1 male offspring. Issue 1 (30th March 2015) - Nohara, Keiko; Okamura, Kazuyuki; Suzuki, Takehiro; Murai, Hikari; Ito, Takaaki; Shinjo, Keiko; Takumi, Shota; Michikawa, Takehiro; Kondo, Yutaka; Hata, Kenichiro
Abstract: Gestational exposure can affect the F2 generation through exposure of F1 germline cells. Previous studies reported that arsenite exposure of only F0 females during their pregnancy increases hepatic tumors in the F1 males in C3H mice, whose males are predisposed spontaneously to develop hepatic tumors later in life. The present study addressed the effects of gestational arsenite exposure on tumorigenesis of the F2 males in C3H mice. Expression analysis of several genes in the normal livers at 53 and 80 weeks of age clearly showed significant changes in the F2 males obtained by crossing gestational arsenite‐exposed F1 (arsenite‐F1 ) males and females compared to the control F2 males. Some of the changes were shown to occur in a late‐onset manner. Then the tumor incidence was assessed at 75–82 weeks of age in the F2 males obtained by reciprocal crossing between the control and arsenite‐F1 males and females. The results demonstrated that the F2 males born to arsenite‐F1 males developed tumors at a significantly higher rate than the F2 males born to the control F1 males, irrespective of exposure of F1 females. Gene expressions of hepatocellular carcinoma markers β‐catenin (CTNNB1) and interleukin‐1 receptor antagonist in the tumors were significantly upregulated in the F2 males born to arsenite‐F1 males compared to those born to the control F1 males. These results show that arsenite exposure of only F0 pregnant mice causes late‐onset changes and augments tumors in the livers of the F2 males by affecting the F1 male offspring. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Gestational exposure can affect the F2 generation through exposure of F1 germ cells. We assessed tumor incidence in the F2 males obtained by reciprocal crossing between the control and gestationally arsenite‐exposed F1 males and females in C3H mice. The results demonstrated that the F2 males born to arsenite‐F1 males developed tumors at a significantly higher rate than the F2 males born to the control F1 males. We also characterized gene expression of several hepatocellular carcinoma markers in the F2 tumors.